Research on Motion Simulation of a Quadruped Bionic Horse Robot Driven by a Cam-link Mechanism - Liangwen Wang; Weiwei Zhang; Liwei Li; Fannian Meng; Tuanhui Wang; Wenliao Du (Jixie chuandong)
A quadruped walking robot with a bionic horse configuration for equestrian-assisted treatment is presented. A single leg system of the robot with two driving degrees of freedom （DOFs） is driven by a cam-linkage combination mechanism， and it can adjust the span and height of the leg end-point trajectory. On the basis of introducing the structure and working principle of the quadruped bionic horse robot driven by a cam-linkage combination mechanism， the movement simulation of the robot is carried out. Using SolidWorks software to establish the bionic horse robot model and import it into Adams software for dynamics simulation. By motion planning to set a motor driving function， the walking movement of the bionic horse robot is realized. From the further analysis， the change law of the contact forces between the foot end and the ground， and the corresponding trend of the motion trajectory are obtained in the process of the leg lift and landing. Aiming at body jumping phenomenon occurring in the simulation movement of the bionic horse robot， a measures of variable driving laws for the motor are put forward to improve the body jumping. The relevant research provides theoretical support for optimization design and application of the robot.